A role for histamine in cardiovascular regulation in late stage embryos of the red-footed tortoise, Chelonoidis carbonaria Spix, 1824 - Crossley II, Dane A.; Sartori, Marina R. [UNESP]; Abe, Augusto S. [UNESP]; Taylor, Edwin W. [UNESP] (My University, 2013)
A chorioallantoic membrane artery in embryos of the red-footed tortoise, Chelonoidis carbonaria was occlusively cannulated for measurement of blood pressure and injection of drugs. Two age groups of embryos in the final 10 % of incubation were categorized by the ratio of embryonic body to yolk mass. All embryos first received cholinergic and β-adrenergic blockade. This revealed that β-adrenergic control was established in both groups whereas cholinergic control was only established in the older group immediately prior to hatching. The study then progressed as two series. Series one was conducted in a subset of embryos treated with histamine before or after injection of ranitidine, the antagonist of H2 receptors. Injection of histamine caused an initial phasic hypertension which recovered, followed by a longer lasting hypertensive response accompanied by a tachycardia. Injection of the H2 receptor antagonist ranitidine itself caused a hypotensive tachycardia with subsequent recovery of heart rate. Ranitidine also abolished the cardiac effects of histamine injection while leaving the initial hypertensive response intact. In series, two embryos were injected with histamine after injection of diphenhydramine, the antagonist to H1 receptors. This abolished the whole of the pressor response to histamine injection but left the tachycardic response intact. These data indicate that histamine acts as a non-adrenergic, non-cholinergic factor, regulating the cardiovascular system of developing reptilian embryos and that its overall effects are mediated via both H1 and H2 receptor types. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Adrenergic; Cardiovascular; Cholinergic; Embryonic; Histamine; Reptilia